METHODOLOGICAL PRINCIPLES OF TEACHING BIOLOGICAL CHEMISTRY IN HIGHER MEDICAL EDUCATION - Makhammadjonov Tursunboy A’zamjon o’g’li (Galaxy International Interdisciplinary Research Journal, 2023)
To substantiate the scientific and pedagogical priority of using innovative pedagogical technologies in the course of teaching clinical biochemistry in higher educational institutions specializing in medicine.